Cytotoxic activity of Fomitopsis betulina against normal and cancer cells – a comprehensive literature review - Paulina Nowotarska; Maciej Janeczek; Benita Wiatrak (Contemporary Oncology)
In recent years, there has been increasing interest in research on fungi, including Fomitopsis betulina, known for its potential therapeutic properties. The aim of this paper is to systematically review the literature on the cytotoxic effects of Fomitopsis betulina on normal and cancer cell lines. The review was conducted by searching PubMed, Google Scholar, and Web of Science databases up to July 2024, using specific MeSH terms and keywords related to cytotoxicity, cancer cells, and normal cells. Articles were included if they investigated both cancer and normal cell cultures, reported IC50 values, and used validated cytotoxicity assays (e.g. MTT, LDH). Out of 450 articles screened, 5 met the inclusion criteria. The analysed studies demonstrated that Fomitopsis betulina extracts, particularly methanolic and ethanolic, exhibited selective cytotoxicity against cancer cells while having minimal impact on healthy cells. The strongest effects were observed in prostate cancer and melanoma cell lines. The cytotoxic effects were largely attributed to bioactive compounds such as triterpenes and glucans. Fomitopsis betulina extracts, particularly those derived from fruiting bodies and mycelial cultures, show promising cytotoxic properties against cancer cells, with limited impact on healthy cells. However, further research is needed to fully understand the mechanisms of action and to optimise extraction methods.